Literary research and the Anglo-Saxon and medieval eras strategies and sources - Booher, Dustin (Literary research ;, 2020)
"Literary Research and the Anglo-Saxon and Medieval Eras: Strategies and Sources is a guide to scholarly research in the field of medieval English literature covering the period 450 CE to 1500 CE. The volume presents the best practices for building a foundation of sound scholarship practices in the field of medieval English literature"--